PENGARUH KUALITAS LAYANAN DAN PROMOSI TERHADAP KEPUASAN PELANGGAN PT ADHI KARYA, TBK - Firmansyah Sulaeman. G; Devi Krisnawati (Program Studi Magister Manajemen Universitas Krisnadwipayana, 2020)
To determine the effect of service quality and promotion on customer satisfaction, PT. Adhi Karya, Tbk. The data used are primary data by giving questionnaires to customers who happen to meet. The analytical method used is simple linear regression analysis and multiple linear regression analysis. The results showed that the quality of service and promotion has a significant effect on customer satisfaction. PT. Adhi Karya, Tbk.